2022
DOI: 10.1080/19491034.2022.2032917
|View full text |Cite
|
Sign up to set email alerts
|

Filament assembly of the C. elegans lamin in the absence of helix 1A

Abstract: Lamins are the major constituent of the nuclear lamina, a protein meshwork underlying the inner nuclear membrane. Nuclear lamins are type V intermediate filaments that assemble into ~3.5 nm thick filaments. To date, only the conditions for the in vitro assembly of Caenorhabditis elegans lamin ( Ce -lamin) are known. Here, we investigated the assembly of Ce -lamin filaments by cryo-electron microscopy and tomography. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Previous cryoelectron microscopy (cryoEM) studies revealed that mature vimentin IFs typically contained four octameric protofibrils with right-handed supertwisting, while considerable structural variability was also observed 14 , 15 . Further cryoEM observations of several IF classes were reported recently 16 19 . However, preparations of such filaments, both extracted from cells and assembled in vitro, suffer from considerable heterogeneity, which has limited the resolution of these studies.…”
Section: Introductionmentioning
confidence: 71%
“…Previous cryoelectron microscopy (cryoEM) studies revealed that mature vimentin IFs typically contained four octameric protofibrils with right-handed supertwisting, while considerable structural variability was also observed 14 , 15 . Further cryoEM observations of several IF classes were reported recently 16 19 . However, preparations of such filaments, both extracted from cells and assembled in vitro, suffer from considerable heterogeneity, which has limited the resolution of these studies.…”
Section: Introductionmentioning
confidence: 71%